Assessing the Knowledge, Attitudes and Behaviors of Human and Animal Health Students towards Antibiotic Use and Resistance: A Pilot Cross-Sectional Study in the UK - Oliver James Dyar; Holly Hills; Lara-Turiya Seitz; Alex Perry; Diane Ashiru-Oredope (MDPI AG, 2018)
The Global Action Plan on Antimicrobial Resistance highlights the importance of training all healthcare professionals. No study has assessed patterns of students' knowledge, attitudes and practices concerning antibiotic use simultaneously across different healthcare course types. We conducted a cross-sectional multi-center survey among UK students. The survey was advertised through local survey coordinators at 25 universities. The online survey was accessible from 10th October to 17th November 2016 (before European Antibiotic Awareness Day). A total of 255 students from 25 universities participated, including students on medicine, pharmacy, nursing, physician associate, dentistry and veterinary medicine courses. Antibiotic resistance was considered to be a more important global challenge than climate change, obesity or food security (p < 0.001). Most students (95%) believed that antibiotic resistance will be a problem for their future practice, but fewer (69%) thought that the antibiotics they will prescribe, administer or dispense will contribute to the problem. A fifth of students felt they had sufficient knowledge of antibiotic use for their future work. Our exploratory study suggests that UK human and animal healthcare students are aware of the importance of antibiotic resistance, but many still have certain misconceptions. Campaigns and improved educational efforts applying behavioral insights methodology could address these.